An investigation of SnO2 nanofilm for solar cell application by spin coating technique. (2021) - Rameshkumar, C.; Anderson, A.; Ananth, D.; Hinduja Mohan, T.; Subalakshmi, R.
Abstract: In this paper, we prepared the transparent nanofilms tin oxide (SnO2 ) by spin coating technique used for solar cell application. The usage of raw materials for fabrication are minimized and hence the costs is optimized. SnO2 is a transparent metal oxide and it has very superior electrical, thermal conducting and optical properties. The efficiency of the solar cell nanofilm depends mainly on the thickness of nanofilm layer. The optimizing parameters such as the solute concentration spin rate, time of the turn table and heat treatment temperature. Nanofilm thickness and heat treatment techniques are to be accounted for good SnO2 thin film production. SnO2 film is prepared from tin (II) chloride dihydrate (SnCl2 ·2H2 O) in ethanol to prepare SnO2 thin films, tin (II) chloride dihydrate as precursor and ethanol as the solvent. Thus, nanofilm coated using spin coating techniques is subjected to various characterization techniques to study the nanofilm layer and its applications. The presence of SnO2 is identified by Fourier-transform infrared spectroscopy (FTIR) and the thickness of the layer is measured by Stylus Profilometer. The composition of the materials in the nanofilm are identified by XRD characterization.